2006
DOI: 10.1111/j.1447-0349.2006.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary team working: Collaboration and conflict

Abstract: The aim of this paper is to report on findings identifying some of the difficulties encountered by the multidisciplinary team in the development and implementation of a care pathway for patients diagnosed with schizophrenia. Policy direction has shifted towards greater team working and blurring of professional boundaries. Moreover, there is greater need to deliver care according to set standards and for patients to reach particular outcomes of care. Care pathways are relatively new for psychiatry and will pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 31 publications
1
59
0
Order By: Relevance
“…However, the nurses in this study underestimated the value their unique care activities would have to nursing handover. Perhaps their activities were not clearly acknowledged within the broader domain of mental health rehabilitation practices or the voice of nurses as a singular group had been 'displaced' by others (Jones 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the nurses in this study underestimated the value their unique care activities would have to nursing handover. Perhaps their activities were not clearly acknowledged within the broader domain of mental health rehabilitation practices or the voice of nurses as a singular group had been 'displaced' by others (Jones 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mental health rehabilitation services utilize a multidisciplinary team approach with collaborative coordination of patient care (Jones 2006;NSW Health Department 2002;Pratt et al 2007). Each professional group contributes their own knowledge and experience, with none seen as being superior over another (Stanton & Tooth 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, one study found that a lack of role clarity could also trigger role blurring, as when a new, poorly defined role was introduced into a team, the post-holder undertook a variety of tasks falling outside of their remit in order to gain acceptance from their colleagues (Willard & Luker, 2007). Role blurring was also strongly influenced by the individual attitudes of team members (Booth & Hewison, 2002;Clarke, 2010;Jones, 2006;Long et al, 2003;Nancarrow, 2004;Proctor-Childs et al, 1998;Smith & Roberts, 2005). For example, those who felt insecure or less confident in their role were more protective of it and less willing to blur role boundaries than those with professional confidence.…”
Section: Role Blurringmentioning
confidence: 95%
“…It is a complex social phenomenon and is recognised in the academic fields of politics, psychology, management and international relations.. Although conflict has been greatly researched in psychology and management it can be argued that it is still in its infancy in the academic field of health and social care (see Elston and Holloway, 2001;Reese and Sontag, 2001;Jones, 2006 andGraboury et al, 2011). Moreover, it has not been extensively used to consider the organisational dynamics that exist within a children's integrated service.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Baxter and Brumfitt (2008) and Jones (2006) denotes the fact that health and social care professionals have their own value base which dictates how they carry out and also accomplish tasks (Carpenter, 2002). As stated earlier, Frost and Robinson (2007 p.191) found that professionals made use of different explanatory frameworks in order to decide upon the task and the nature of the intervention; for example social work practitioners made use of the developmental risk and protection model, health service practitioners the medical model and educationalist an attainment model.…”
Section: Practitioners" (Respondent A)mentioning
confidence: 99%